Efektivitas Terapi Metformin dalam Mencapai Target Kadar HbA1c - Ni Kadek Ayu Kunti Pertiwi; Lisa Kurnia Sari; Hendi Wicaksono; Tejo Jayadi (Yayasan Literasi Sains Indonesia, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease with high prevalence in Indonesia, include Bantul Regency,Yogyakarta. In September 2024 the number of cases reached 18,520, indicating a high disease burden at the primary healthcare level. At Puskesmas Imogiri 1, most T2DM patients receive metformin therapy, yet the coverage of care and effectiveness of treatment in achieving optimal glycemic control, particularly HbA1c levels, remain challenging in daily practice. This study aimed to assess the effectiveness of metformin dosage in achieving HbA1c <7% in T2DM patients at Puskesmas Imogiri 1. A quantitative study with a cross-sectional design and total sampling technique was conducted among T2DM patients treated at this facility. The variables studied included type and dosage of metformin therapy and HbA1c levels as indicators of glycemic control, with data collected from medical record reviews, including medication history and the most recent HbA1c test results. Of the 54 respondents, 35.2% achieved HbA1c <7%, while the majority remained above the target. Statistical analysis using Fisher’s Exact Test revealed no significant association between metformin dosage and glycemic control status. Likewise, duration of therapy, sex, and age were not significantly associated with HbA1c achievement (p>0.05). In conclusion, this study indicates that there is no significant relationship between metformin dosage, duration of therapy, age, or sex and the achievement of HbA1c targets in T2DM patients at Puskesmas Imogiri 1.